Health behaviour change theories: Contributions to an ICF-based behavioural exercise therapy for individuals with chronic diseases - Geidl, Wolfgang; Semrau, Jana; Pfeifer, Klaus (Disability and Rehabilitation, 2014)
Purpose: The purpose of this perspective is (1) to incorporate recent psychological health behaviour change (HBC) theories into exercise therapeutic programmes, and (2) to introduce the International Classification of Functioning (ICF)-based concept of a behavioural exercise therapy (BET).
UnivIS-Import:2015-03-09:Pub.2014.phil.dps.iss.psbg.health
Keywords: Chronic non-communicable disease; Integrative approach; Personal factors; Physical activity; Physical therapy; Rehabilitation